How animals behave : a new look at wildlife. - National Geographic Society (U.S.) ([Washington, D.C.] : National Geographic Society, 1984)
Explains how different animals obtain their food, protect themselves, court a mate, care for their eggs and their young, and live together. Includes profiles of animal behaviorists and research methods they have used.
Includes index.
Bibliography: p. 103.
Keywords: Animal behavior -- Juvenile literature; Animals -- Habits and behavior